Tuning the interface between poly(vinylidene fluoride)/UV-curable polysilsesquioxane hybrid composites: Compatibility, thermal, mechanical, electrical, and surface properties - Cho, Kie Yong; Lee, Albert S.; Jeon, Hyeonyeol; Park, Sang-Hee; Jang, Munjeong; Yoon, Ho Gyu; Hong, Soon Man; Baek, Kyung-Youl; Hwang, Seung Sang (ELSEVIER SCI LTD, 2015)
Compatible hybrid composites (PVLPMA) comprising of poly(vinylidene fluoride) (PVDF) and UV-curable ladder-like polysilsesquioxane (LPMASQ) were investigated for maximizing synergetic effects in various properties. The PVDF fluoropolymer was found to be well-incorporated with the LPMASQ inorganic filler because of good hydrogen-bonding, and the compatibility rigorously investigated by FT-IR, DSC, and WAXS studies. In addition, the crosslinkable function arising from the methacryl-group of the LPMASQ inorganic filler with the aid of the radical source was evaluated from the analysis of various properties. After UV-crosslinking, PVLPMA hybrid composites showcased enhanced mechanical properties such as elastic modulus, surface modulus, and surface hardness with accordance to the increasing the LPMASQ quantity. In addition, hydrophobicity was observed through the increase in the water contact angle up to 115 degrees, a value much larger than that of neat PVDF and cured LPMASQ. Furthermore, the enhanced electrical stability of PVLPMA hybrid composites was obtained through examination of dielectric properties and breakdown strength in comparison to neat PVDF. These PVDF-LPMASQ organic-inorganic compatible hybrid composites with enhanced properties arising from the good compatibility and synergetic effects can be applicable in the various fields supplanting neat PVDF. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: POLYMER; NANOCOMPOSITES; NANOTUBES; MEMBRANE; DESIGN